Long-term outcomes of delayed percutaneous coronary intervention for patients with ST-segment elevation myocardial infarction: A propensity score-matched retrospective study. Issue 46 (19th November 2021) - Xue, Yu-Long; Ma, Yue-Teng; Gao, Yu-Ping; Zhang, Sheng-Xiao; Su, Qin-Yi; Li, Yu-Feng; Zhang, Lei; Ding, Peng-Fei; Li, Xue-Wen
Abstract : Abstract: The best time window of percutaneous coronary intervention (PCI) is within 12 hours for ST-segment elevation myocardial infarction (STEMI). However, there is limited evidence about the proper time of PCI for delayed STEMI patients. From June 2014 to June 2015, a total of 268 patients receiving PCI with second-generation drug-eluting stent in a Chinese hospital after 3 days of STEMI onset were enrolled in this retrospective study, who were divided into the early group (3–14 days) and the late group (>14 days). A propensity score match was conducted to reduce the baseline difference. The primary endpoint of all-cause death and secondary endpoints of major adverse cardiac and cerebrovascular event (myocardial infarction [MI], stroke, emergent revascularization, and rehospitalization due to heart failure) were compared using survival analysis. At last, 182 cases were matched after propensity score match, with no statistical difference in baseline characteristics and PCI data. Kaplan-Meier survival curve demonstrated no difference in all-cause death of the 2 groups ( P = .512). However, the early group presented a higher incidence of MI than the late group ( P = .036). The multivariate Cox regression analysis also demonstrated that the early PCI was an independent risk factor for MI compared with late PCI (hazard ratio = 3.83, 95%CI [1.91–8.82], P = .001). There was no statistical difference in other major adverse cardiac and cerebrovascular event, including stroke, emergent revascularization, and rehospitalization due to heart failure. Using the 2 nd drug-eluting stent, early PCI (3–14 days) and late PCI (>14 days) have comparable efficacy and outcomes. However, patients receiving early PCI are subjected to a relatively higher risk of recurrent MI.